Seeds on ice : Svalbard and the Global Seed Vault - Fowler, Cary (Prospecta Press, an imprint of Easton Studio Press, 2016)
Closer to the North Pole than to the Arctic Circle, on an island in a remote Norwegian archipelago, lies a vast global seed bank buried within a frozen mountain. At the end of a 130-meter long tunnel chiseled out of solid stone is a room filled with humanity's precious treasure, the largest and most diverse seed collection ever assembled: more than a half billion seeds containing the world's most prized crops, a safeguard against catastrophic starvation. The Global Seed Vault, a visionary model of international collaboration, is the brainchild of Cary Fowler, renowned scientist, conservationist, and biodiversity advocate. In SEEDS ON ICE, Fowler tells for the first time the comprehensive inside story of how the "doomsday seed vault" came to be, while the breathtaking photographs offer a stunning guided tour not only of the private vault, but of the windswept beauty and majesty of Svalbard and the enchanting community of people in Longyearbyen. With growing evidence that unchecked climate change will seriously undermine food production and threaten the diversity of crops around the world, SEEDS ON ICE offers a personal and passionate reminder that we shouldn't take our reliance on the world of plants for granted--and that, in a very real sense, the future of the human race rides on this frozen and indispensable biodiversity.